Pengaruh Variasi Dosis Penambahan Biochar Sekam Padi Terhadap Efisiensi Penyisihan Logam Berat Cd Pada Tanah Tercemar - Fajri, Sandra Monica; Sasmita, Aryo; Elystia, Shinta (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Biochar has a large surface area, and a high capacity to absorb heavy metals and can potentially be used to reduce bioavailability and leach of heavy metals as well as organic pollutants in the soil through adsorption. This study aims to determine the effect of adding biochar from rice husks to removal of heavy metals Cd in contaminated soil. Biochar is made using a pyrolysis apparatus with a burning temperature of 500oC for 1 hour. The dose variation used in this study was 10% ; 12.5% ; and 15% with 30 days incubation periods. The results showed that the highest Cd removal occurred at the addition of a 15% dose of biochar, so that the concentration of heavy metal Cd became 10.85 mg/kg with a removal efficiency of 45.45%. Key words: biochar, rice husk, biochar dose, polluted soil, heavy metals